Developing Test For Experimental Study: The Effectiveness Of Hedwig Strategy In English Education Department University Brawijaya - Ratri, Devinta Puspita; Hapsari, Yulia; Adi, Sugeng Susilo (LPPM Universitas Mercu Buana Yogyakarta, 2016)
AbstractHaving a big number of students in content subject of a language class is a challenge for teacher since it is quite difficult to accommodate students’ critical thinking and active participation at the same time. Therefore, Hedwig strategy is aimed to give room for students to explore themselves and get involved in the materials delivered in the class. Furthermore, by having group and regroup to deliver message in Hedwig strategy, students are forced to be active participated in classroom activities. The idea of Hedwig strategy is inspired by Jigsaw and Think-Pair-Share which have existed before. To know whether Hedwig strategy is effectively applied in content subject in large language class, it is proposed to do quasi experimental study with one class as an experimental group and one class as a control group. The experimental group is treated by using Hedwig strategy. Prior to the experimental study, it is performed research and development to develop the test for pre-test and post-test. For that reason, the research problem is what test is valid and reliable for an experimental study on the effectiveness of Hedwig strategy for the 4th semester students in Language Teaching Methodology class in English Education Department Universitas Brawijaya. This research reports half of the whole plan where the researchers developed test for pre-test and posttest to measure students’ improvement in understanding Language Teaching Methodology. In short, the test developed in this study will be used to carry out experimental study as pre-test and post-test